The Strategic Role of the National Cyber and Crypto Agency (BSSN) in Maintaining State Sovereignty in Cyberspace - Aji, Muhammad Prakoso; Somantri, Gumilar Rusliwa; Rofii, Muhammad Syaroni (Dinasti Research, 2025)
The development of technology places data in cyberspace as a very valuable commodity. In the political aspect, seeing data sovereignty is a fundamental foundation in realizing state sovereignty in cyberspace. A country's data sovereignty is faced with the position of the state with the private sector in a global context. Cybersecurity systems and data sovereignty are inseparable in achieving state sovereignty in cyberspace. The main role of the state is to realize protection and maintain data security in national cyberspace. In 2017, the Government established the National Cyber and Crypto Agency (BSSN) which is a transformation of the National Crypto Agency which was combined with several other government agency work units related to cybersecurity. The presence of BSSN provides a very strategic key role in maintaining state sovereignty in cyberspace. This is in line with global challenges where cyber attacks and data leaks are increasingly rampant in Indonesia. For this reason, this study will explain the strategic role of BSSN in maintaining data sovereignty in order to realize state sovereignty in cyberspace. The author uses state theory and the concept of data sovereignty in analyzing this. The author uses qualitative methods to collect data through various literature studies, such as: books, journal articles, and other reference sources. The results of the study show that BSSN is a representation of the state's presence in maintaining the sovereignty of national cyberspace. This can be seen from the increase in Indonesia's cybersecurity index on a global scale which reflects an increase in national cybersecurity capabilities